Conservative Management of Congenital Eversion of the Upper Lid in a Nigerian Child - B.O. Omolase, A. Ogedengbe, C.O. Omolase, O.T. Ogunleye (Pakistan Journal of Ophthalmology, 2018)
This is a case report of a male Nigerian child who was brought to the eye centre of Federal Medical Cente, Owo, Ondo State, Nigeria by his mother and concerned relatives three hours after delivery at a maternity centre in a nearby town in May, 2011. The child was noticed to have eversion of both the upper eyelids, most prominent on the left immediately after an uncomplicated spontaneous vaginal delivery following a full term uneventful pregnancy. Conservative management instituted led to resolution of the lid eversion within four days of presentation.